INSURGENCY IN THE 1990s: THE CASE OF TRIPURA - Rajib Das (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
Since its merger with the Indian Union in 1949, Tripura, a tiny north-eastern Indian state, has seen an increase in insurgent activities led by its educated tribal middle class. During the post-merger era, the newly formed educated tribal middle class felt disgruntled with the government’s anti-tribal policies and actions. The new Indian Constitution of 1950 did not include a provision for Tripura’s tribal areas to have their own autonomous district. The Tripura Land Revenue and Land Reform Act of 1960 made no provision for Maharaja Bir Bikram Kishore’s "tribal reserve." Bengali was designated as the official language of Tripura by the Official Language Act of 1962. These are the major reasons that led to the genesis of many tribal-centric insurgent groups. During the period covered by this study, the 1990s, many insurgent groups, such as the NLFT, ATTF, and others, launched various activities challenging state authorities to meet their demands or risk overthrowing the state administration. In this paper, I tried to provide a picture of insurgent activities that happened in Tripura during the period under this study.